Low Cost Microcontroller Based TIC TAC TOE Game - Al Wesabi, Mohammed; Saif, Eiad; Al Kustaban, Ameen (University of Science and Technology, Yemen, 2015)
TIC TAC TOE is a commonly traditional game in Yemen, which consists of two players. One of the player chooses a cell of the game and puts an X mark in the chosen cell while the second player chooses another cell and puts an O mark in this second cell. The purpose of the paper is to transport this commonly traditional game to modern electronic game to get along with modern electronic world. The modern electronic game is important to countryside childrens, so that they can play the game safely without incurring diseases. It also aims to offer children an opportunity to deal with cheap modern techniques. The game designed in this paper is based on the microcontroller (PIC16f877A).